2019
DOI: 10.1155/2019/1251295
|View full text |Cite
|
Sign up to set email alerts
|

Calculation Method of Seismic Residual Displacement of Sheet Pile Quay Walls

Abstract: Sheet pile quay walls have widely been used in port engineering, hydraulic engineering, and civil engineering, but the sheet pile quay is a flexible retaining structure, which undergoes large deformation during earthquakes. The seismic design methods of the sheet pile quay wall in different countries are greatly different, and there is deficit of studies performed on the seismic residual displacement of the sheet pile quay walls. Based on the pseudostatic method and the calculation method for obtaining the dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Conventional seismic design of anchor piles generally only considers tie rod tension and subgrade reaction as loads acting on the anchor piles [1]. Although this conventional method has been effective for designing safe cross-sections of piles to resist seismic forces, it predicts the deformation degree with low accuracy [7,8]. Various studies have shown that two-dimensional (2D) Finite Element Analysis (FEA) can accurately reproduce the seismic deformation of quay walls [9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Conventional seismic design of anchor piles generally only considers tie rod tension and subgrade reaction as loads acting on the anchor piles [1]. Although this conventional method has been effective for designing safe cross-sections of piles to resist seismic forces, it predicts the deformation degree with low accuracy [7,8]. Various studies have shown that two-dimensional (2D) Finite Element Analysis (FEA) can accurately reproduce the seismic deformation of quay walls [9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Also, when the top layer or layers of soil are highly compressible or very weak so that the shallow foundation cannot be used to distribute the structural load, pile foundations are used to transfer the load to the stiffer bottom layers or bedrock. When the bedrock or stiffer bottom layers are at the deeper depth below the soil surface, the pile is used for the gradual transfer of the loads [1,2]. Depending on the load type, soil, and structural conditions (such as dimensions of structure, distance between piles in a pile group, distance of the structure from bedrock and soil surface, definition of interaction type between structure and surrounding soil, etc.…”
Section: Introductionmentioning
confidence: 99%